Advocacy and archaeology : urban intersections - Britt, Kelly M.; George, Diane F. (Berghahn Books, 2023)
"Archaeologists have a history of being prime agents of change, particularly in advocating for protection and preservation of historical resources. As more social issues intersect with archaeology and historical sites, we see archaeologists and others continuing to advocate for not only historic resources, but for the larger social justice issues that threaten the communities in which these resources reside. Inspired by the idea of revolution and excitement about the ways archaeology is being used in social justice arenas, this volume seeks to visualize archaeology as part of a movement by redefining what archaeology is and does for the greater good"-- Provided by publisher.
Keywords: Urban archaeology.; Archaeology -- Social aspects.; Archaeology -- Political aspects.; Social justice.; Archaeology and history.; Archéologie urbaine.; Archéologie -- Aspect social.; Archéologie -- Aspect politique.; Justice sociale.; Archéologie et histoire.; historical archaeology.; SOCIAL SCIENCE / Archaeology; Archaeology and history; Archaeology -- Political aspects; Archaeology -- Social aspects; Social justice; Urban archaeology; Electronic books.